Tax Administration Technology and Taxpayer Compliance - Winoto, Lorensia Octaviani; Dewi, Dian Indu; Prihantini, Febrina Nafasati (Universitas Semarang, 2022)
The government, specifically the Directorate General of Taxes, applies technology in the administration of taxation to facilitate the public in reporting taxes. E-registration, e-billing, and e-filling have become a form of application of tax administration technology. The application of this technology is expected to help while improving taxpayer compliance in reporting taxes owed.This research is quantitative research using primary data. Respondents are private taxpayers who have a Taxpayer Identification Number (NPWP) and are registered with KPP Pratama Semarang Selatam and KPP Semarang Tengah Satu. Analysis of research data using multiple linear regression methods with the statistic tool of the SPSS program version 23.Statistical test results show there are no constraints in the classical assumption test. The results of hypothesis testing show that all hypotheses are accepted, namely that E-registration, e-billing, and e-filling have a positive effect on taxpayer compliance.